Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus Nsp4 Cleaves VISA to Impair Antiviral Responses Mediated by RIG-I-like Receptors - Huang, C.; Du, Y. P.; Yu, Z. B.; Zhang, Q.; Liu, Y. H.; Tang, J.; Shi, Jishu; Feng, W. H. (My University, 2016)
Porcine reproductive and respiratory syndrome virus (PRRSV) is one of the most significant etiological agents in the swine industry worldwide. It has been reported that PRRSV infection can modulate host immune responses, and innate immune evasion is thought to play a vital role in PRRSV pathogenesis. In this study, we demonstrated that highly pathogenic PRRSV (HP-PRRSV) infection specifically down-regulated virus-induced signaling adaptor (VISA), a unique adaptor molecule that is essential for retinoic acid induced gene-I (RIG-I) and melanoma differentiation associated gene 5 (MDA5) signal transduction. Moreover, we verified that nsp4 inhibited IRF3 activation induced by signaling molecules, including RIG-I, MDA5, VISA, and TBK1, but not IRF3. Subsequently, we demonstrated that HP-PRRSV nsp4 down-regulated VISA and suppressed type I IFN induction. Importantly, VISA was cleaved by nsp4 and released from mitochondrial membrane, which interrupted the downstream signaling of VISA. However, catalytically inactive mutant of nsp4 abolished its ability to cleave VISA. Interestingly, nsp4 of typical PRRSV strain CH-1a had no effect on VISA. Taken together, these findings reveal a strategy evolved by HP-PRRSV to counteract anti-viral innate immune signaling, which complements the known PRRSV-mediated immune-evasion mechanisms.
Citation: Huang, C., Du, Y. P., Yu, Z. B., Zhang, Q., Liu, Y. H., Tang, J., . . . Feng, W. H. (2016). Highly Pathogenic Porcine Reproductive and Respiratory Syndrome Virus Nsp4 Cleaves VISA to Impair Antiviral Responses Mediated by RIG-I-like Receptors. Scientific Reports, 6, 13. https://doi.org/10.1038/srep28497
Keywords: Pattern-Recognition Receptors; Interferon-Stimulated Genes; Innate; Immune-Responses; Nonstructural Protein 4; Toll-Like Receptors